Functional Toxicogenomic Profiling Expands Insight into Modulators of Formaldehyde Toxicity in Yeast - North, Matthew; Gaytán, Brandon D.; Romero, Carlos; De La Rosa, Vanessa Y.; Loguinov, Alex; Smith, Martyn T.; Zhang, Luoping; Vulpe, Chris D. (Frontiers in Genetics, 2016)
Formaldehyde (FA) is a commercially important chemical with numerous and diverse uses. Accordingly, occupational and environmental exposure to FA is prevalent worldwide. Various adverse effects, including nasopharyngeal, sinonasal, and lymphohematopoietic cancers, have been linked to FA exposure, prompting designation of FA as a human carcinogen by U.S. and international scientific entities. Although the mechanism(s) of FA toxicity have been well studied, additional insight is needed in regard to the genetic requirements for FA tolerance. In this study, a functional toxicogenomics approach was utilized in the model eukaryotic yeast Saccharomyces cerevisiae to identify genes and cellular processes modulating the cellular toxicity of FA. Our results demonstrate mutant strains deficient in multiple DNA repair pathways–including homologous recombination, single strand annealing, and postreplication repair–were sensitive to FA, indicating FA may cause various forms of DNA damage in yeast. The SKI complex and its associated factors, which regulate mRNA degradation by the exosome, were also required for FA tolerance, suggesting FA may have unappreciated effects on RNA stability. Furthermore, various strains involved in osmoregulation and stress response were sensitive to FA. Together, our results are generally consistent with FA-mediated damage to both DNA and RNA. Considering DNA repair and RNA degradation pathways are evolutionarily conserved from yeast to humans, mechanisms of FA toxicity identified in yeast may be relevant to human disease and genetic susceptibility.